The Effect of Digital Gamified Learning on Fifth Graders’ Critical Thinking in Fraction Arithmetic: A Motivation-Based Moderation Study - Widhia Purnawan; Karsono Karsono; Eka Budhi Santosa (The Eastasouth Journal of Learning and Educations, 2026)
Elementary students’ limited critical thinking in fraction arithmetic remains a persistent concern, particularly when mathematics instruction emphasizes procedural computation rather than reasoning, justification, and evaluation. Digital gamified learning offers a promising alternative, yet its effectiveness may depend on students’ motivational characteristics. This research aimed to examine the effect of digital gamified learning on fifth graders’ critical thinking in fraction arithmetic and to determine whether learning motivation moderated this effect. A quantitative quasi-experimental design with a non-equivalent pretest–posttest control group and a 2 × 2 factorial structure was employed. The participants were 89 fifth-grade students from four public elementary schools in Cepogo District, Boyolali Regency, Central Java, Indonesia. The experimental group received digital gamified learning using Wayground, whereas the control group received PowerPoint-based instruction. Data were collected using a critical thinking test and a learning motivation questionnaire, both of which demonstrated acceptable validity and reliability. The results showed that students in the experimental group achieved a higher mean gain score than those in the control group. Factorial ANCOVA further revealed significant effects of instructional media, learning motivation, and their interaction on students’ posttest critical thinking scores. Students with high learning motivation benefited most from digital gamified learning, although low-motivation students also showed meaningful improvement. These findings imply that digital gamification can serve as an effective instructional strategy for enhancing mathematical critical thinking when it is pedagogically aligned with reasoning-based tasks, immediate feedback, and motivationally responsive learning support.